1994
DOI: 10.1055/s-2007-1021117
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Proteins and Iron Status in Blood as Indicators of the Nutritional Status of 10- to 12-Year-Old Bolivian Boys

Abstract: The purpose of the present study was to evaluate the nutritional status of children based on anthropometric measurements, biochemical indicators of protein energy malnutrition as well as hematological variables. The subjects were 93 10- to 12-year-old Bolivian boys: 12 HAHSES, 28 HALSES, 36 LALSES, and 17 LALSES (see Introduction to this Supplement). The overall nutritional status of the boys was evaluated by anthropometric indicators (weight for age [W/A], height for age [H bd, and weight for height [W/H]). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…Four papers (14,36,40,52) examined values in Japanese populations, two of which presented sufficient data to show that there were no differences among the Caucasian groups (for TSAT (40) or for serum iron (52)). Five additional studies reported values from Caucasian but ethnically restricted national populations (23,41,43,53,56). In two studies (41,53) there were sufficient data to show that there were no differences between serum iron and TSAT in a Caucasian population.…”
Section: Ethnic Group-specific Reference Rangesmentioning
confidence: 94%
See 3 more Smart Citations
“…Four papers (14,36,40,52) examined values in Japanese populations, two of which presented sufficient data to show that there were no differences among the Caucasian groups (for TSAT (40) or for serum iron (52)). Five additional studies reported values from Caucasian but ethnically restricted national populations (23,41,43,53,56). In two studies (41,53) there were sufficient data to show that there were no differences between serum iron and TSAT in a Caucasian population.…”
Section: Ethnic Group-specific Reference Rangesmentioning
confidence: 94%
“…Two studies did not provide information on the ages of the study subjects (38,56). The remaining 29 studies were considered acceptable.…”
Section: Number Of Studies Available For Analysismentioning
confidence: 98%
See 2 more Smart Citations
“…Although sparse knowledge is available on the contribution of economic status to maternal nutritive state during pregnancy at either low or high altitude, independent studies have reported the unremarkable finding that individuals from low socioeconomic status are under-nourished and that those from high socioeconomic status are well-nourished in Andean countries (36,37).…”
Section: Discussionmentioning
confidence: 99%